Investigation of ion and electron heat transport of high-Te ECH heated discharges in the large helical device. (28th January 2016) - Pablant, N A; Satake, S; Yokoyama, M; Gates, D A; Bitter, M; Bertelli, N; Delgado-Aparicio, L; Dinklage, A; Goto, M; Hill, K W; Igamai, S; Kubo, S; et al.
Abstract: An analysis of the radial electric field and heat transport, both for ions and electrons, is presented for a high- electron cyclotron heated (ECH) discharge on the large helical device (LHD). Transport analysis is done using thetask3d transport suite utilizing experimentally measured profiles for both ions and electrons. Ion temperature and perpendicular flow profiles are measured using the recently installed x-ray imaging crystal spectrometer diagnostic (XICS), while electron temperature and density profiles are measured using Thomson scattering. The analysis also includes calculated ECH power deposition profiles as determined through thetravis ray-tracing code. This is the first time on LHD that this type of integrated transport analysis with measured ion temperature profiles has been performed without NBI, allowing the heat transport properties of plasmas with only ECH heating to be more clearly examined. For this study, a plasma discharge is chosen which develops a high central electron temperature ( keV) at moderately low densities ( m −3 ). The experimentally determined transport properties fromtask3d are compared to neoclassical predictions as calculated by thegsrake andfortec-3d codes. The predicted electron fluxes are seen to be an order of magnitude less than the measured fluxes, indicating that electron transport is largely anomalous, while the neoclassical and measured ion heat fluxes are of the same magnitude. Neoclassical predictions of a strong positive ambipolar electric field ( ) in the plasma core are validated through comparisons to perpendicular flow measurements from the XICS diagnostic. This provides confidence that the predictions are producing physically meaningful results for the particle fluxes and radial electric field, which are a key component in correctly predicting plasma confinement.